IMPLEMENTATION OF DECISION MAKING BY HEADMASTER IN IMPROVING TEACHERS 'PEDAGOGIC AND PROFESSIONAL COMPETENCIES IN SENIOR HIGH SCHOOL AL-WASHLIYAH JOHOR MEDAN BUILDING - Daulay, Nurika Khaliala; Salim, Salim; Rahman, Saiful (Universitas Dharmawangsa Medan, 2020)
The purpose of this study was to determine the programs of the head of the madrasah, the condition of the existing teachers in school, and the strategies used by the head of the madrasah to improve the competence of teachers at Madrasah Aliyah Al Washliyah, Johor Medan Building. This research uses descriptive qualitative research with a phenomenological approach that uses observation, interview, and documentation study techniques to obtain data from research informants, namely: the principle of the Aliyah Al-Washliyah madrasah, administration, and 5 teachers at the madrasah aliyah Al-Washliyah, Johor Medan Building. This study uses data analysis techniques with the interactive analysis technique of the Miles and Huberman model, with the main components of the analysis, namely data reduction, data display and conclusion/verification, and checking the validity of the data in this study including Credibility Test, Transferability Test, Dependency Test, and Test. Certainty. The findings in the research obtained are as follows: (1) Decision-making strategies improve teacher pedagogical and professional competence through a decision based on the results of selecting several alternative problems that have been determined for the achievement of madrasah goals. Making these decisions includes identifying problems, formulating problems, and selecting alternative decisions based on calculations and various aspects that may arise. At the implementation or operational stage, the head of the madrasah as a leader must make many routine decisions to control activities following the plans and conditions in force. Whereas in the supervision stage, namely monitoring, checking, and evaluating the results of implementation is carried out to evaluate the implementation and decision making that have been made (2) programs of madrasah principals in improving teacher pedagogical and professional competence, including: Providing libraries, involving Workshop Teachers, supervision, giving awards, Personal Communication between Principals and Teachers, training, School Level MGMP Activities and Ministry of Religion coaching. (3) conditions of pedagogic and professional competence of teachers in madrasah al washliyah, building Johor Medan, including madrasah head and teacher teachers who are in good condition including teachers who have professional competence seen from all teachers who already have certification, appropriate qualifications and some already have S2 and continue to the next level have certification, appropriate academic qualifications and some already have S2 and continue to the next level.bThe results of the data analysis concluded: the implementation of Madrasah principals in improving pedagogical and professional competence in Madrasah Aliyah Al Washliyah, johor medan buildings were classified as successful because of the running of the program designed by the head of the madrasah, as well as the decision making of the head of the madrasah in implementing policies was successful by taking steps with attention ethics and discipline of school culture. conditions of academy qualifications, certification, training, are already in place. Even so, some shortcomings exist in the madrasah, such as the infrastructure is not very complete, but all of these are not an obstacle in carrying out the wheels of education in the school.